Redescription of Milnesium alpigenum Ehrenberg, 1853 (Tardigrada: Apochela) and a description of Milnesium inceptum sp. nov., a tardigrade laboratory model - Morek, Witold; Suzuki, Atsushi C.; Schill, Ralph O.; Georgiev, Dilian; Yankova, Maria; Marley, Nigel J.; Michalczyk, Łukasz (Zootaxa, 2019)
Intra- and interspecific variability, being at the very core of alpha taxonomy, has been a long-standing topic of debate among tardigrade taxonomists. Early studies tended to assume that tardigrades exhibit wide intraspecific variation. However, with more careful morphological studies, especially those incorporating molecular tools that allow for an independent verification of species identifications based on phenotypic traits, we now recognise that ranges of tardigrade intraspecific variability are narrower, and that differences between species may be more subtle than previously assumed. The taxonomic history of the genus Milnesium, and more specifically that of the nominal species, M. tardigradum described by Doyère in 1840, is a good illustration of the evolution of views on intraspecific variability in tardigrades. The assumption of wide intraspecific variability in claw morphology led Marcus (1928) to synonymise two species with different claw configurations, M. alpigenum and M. quadrifidum, with M. tardigradum. Currently claw configuration is recognised as one of the key diagnostic traits in the genus Milnesium, and the two species suppressed by Marcus have recently been suggested to be valid. In this study, we clarify the taxonomic status of M. alpigenum, a species that for nearly a century was considered invalid. We redescribe M. alpigenum, using a population collected from the locus typicus, by the means of integrative taxonomy, i.e. including light microscopy, scanning electron microscopy, ontogenetic observations, and genetic barcoding. Moreover, the redescription of M. alpigenum allowed us to verify the uncertain taxonomic status of two popular laboratory models that were originally considered to be M. tardigradum; though one was recently reidentified as M. cf. alpigenum. Our analysis showed that both laboratory strains, despite being morphologically and morphometrically nearly identical to M. alpigenum, in fact represent a new species, M. inceptum sp. nov.  The two species, being disnguishable only by statistical morphometry and/or DNA sequences, are the first example of pseudocryptic species in tardigrades.